Effects of CYP2C19 genetic polymorphism on the pharmacokinetics of tolperisone in healthy subjects - Cho, Chang‑Keun; Byeon, Ji-Young; Kang, Pureum; Park, Hye-Jung; Ko, Eunvin; Mu, Chou Yen; Jang, Choon-Gon; Lee, Seok-Yong; Lee, Yun Jeong (Archives of pharmacal research, 2023)
Tolperisone hydrochloride is a centrally-acting muscle relaxant used for relieving spasticities of neurological origin and muscle spasms associated with painful locomotor diseases. It is metabolized to the inactive metabolite mainly by CYP2D6 and, to a lesser extent, by CYP2C19 and CYP1A2. In our previous study, the pharmacokinetics of tolperisone was significantly affected by the genetic polymorphism of CYP2D6 , but the wide interindividual variation of tolperisone pharmacokinetics was not explained by genetic polymorphism of CYP2D6 alone. Thus, we studied the effects of CYP2C19 genetic polymorphism on tolperisone pharmacokinetics. Eighty-one subjects with different CYP2C19 genotypes received a single oral dose of 150 mg tolperisone with 240 mL of water, and blood samples were collected up to 12 h after dosing. The plasma concentration of tolperisone was measured by a liquid chromatography-tandem mass spectrometry system. The CYP2C19PM group had significantly higher C max and lower CL/F values than the CYP2C19EM and CYP2C19IM groups. The AUC inf of the CYP2C19PM group was 2.86-fold and 3.00-fold higher than the CYP2C19EM and CYP2C19IM groups, respectively. In conclusion, the genetic polymorphism of CYP2C19 significantly affected tolperisone pharmacokinetics.